2015
DOI: 10.1634/theoncologist.2014-0299
|View full text |Cite
|
Sign up to set email alerts
|

Diastolic Dysfunction Occurs Early in HER2-Positive Breast Cancer Patients Treated Concurrently With Radiation Therapy and Trastuzumab

Abstract: Background. Left ventricular ejection fraction (LVEF) is used routinely to monitor cardiac dysfunction associated with breast cancer treatment. In this study the prevalence of early left ventricular diastolic dysfunction (LVDD) and its relationship to the dose-volume of the heart irradiated were evaluated in HER2-positive breast cancer patients undergoing concurrent trastuzumab and adjuvant radiotherapy (RT). Materials and Methods. Data from 40 breast cancer patients treated with concurrent trastuzumab and lef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 47 publications
1
25
1
Order By: Relevance
“…E can be corrected for the influence of preload and relaxation by dividing it by e', and the resulting E/e' ratio has been demonstrated to be the best index to detect LVDD (86%) in heart failure with preserved ejection fraction (HFpEF) in human patients who also had LVDD diagnosed via invasive conductance catheter derived pressure-volume loop (PVL) analyses. 49 Our data suggests that diastolic function may decline fairly soon after TBI exposure, which has also been noted in human breast cancer patients receiving contemporary radiotherapy 57 , and that effects on cardiac volumetric measures may require more time to develop as we only observed differences in the LT IRR vs. LT CTLs.…”
Section: Histological and Immunohistochemical Staining Of The Left Vesupporting
confidence: 57%
“…E can be corrected for the influence of preload and relaxation by dividing it by e', and the resulting E/e' ratio has been demonstrated to be the best index to detect LVDD (86%) in heart failure with preserved ejection fraction (HFpEF) in human patients who also had LVDD diagnosed via invasive conductance catheter derived pressure-volume loop (PVL) analyses. 49 Our data suggests that diastolic function may decline fairly soon after TBI exposure, which has also been noted in human breast cancer patients receiving contemporary radiotherapy 57 , and that effects on cardiac volumetric measures may require more time to develop as we only observed differences in the LT IRR vs. LT CTLs.…”
Section: Histological and Immunohistochemical Staining Of The Left Vesupporting
confidence: 57%
“…The main limitation of current study is that LVEF is not sensitive enough to detect early and minor cardiac dysfunction, thus the actual toxicity might be underestimated. Our group has also explored the role of diastolic function in monitoring early cardiac abnormalities under the same clinical scenario [ 44 ]. Nevertheless, as a fundamental parameter of cardiac function, LVEF is less susceptible to intra-observer differences.…”
Section: Discussionmentioning
confidence: 99%
“…In the case of concomitant SF and anti‐HER‐2 therapy, a small prospective study by Raben et al following 35 patients treated with SF RT with or without concurrent trastuzumab did not show excess RT toxicity in patients who received trastuzumab concurrently with RT, as compared to patients who did not receive trastuzumab . However, in a small prospective study, Cao et al reported higher rates of left ventricular diastolic dysfunction in patients receiving concurrent trastuzumab and RT vs RT alone . Nevertheless, a subsequent retrospective study by Cao et al reported internal mammary chain RT and starting trastuzumab during RT as the only independent risk factors for absolute LVEF decrease, and RT was not found to be a risk factor for cardiac toxicity on multivariate analysis of the N9831 trial investigating cardiac toxicity in patients receiving adjuvant chemotherapy with trastuzumab …”
Section: Discussionmentioning
confidence: 99%